Long-term durable response to Sintilimab therapy in synchronous lung squamous cell carcinoma and gastric adenocarcinoma: a rare case report - Mekuriya Bassaye, Margaret; Jijian, Zou; Li, Zhou; Han, Shuai (Frontiers in Oncology, 2026)
Gastric cancer (GC) and lung squamous cell carcinoma (SCC) are major global causes of cancer-related morbidity and mortality, but their synchronous occurrence is exceedingly rare and poses substantial diagnostic and therapeutic challenges. This report describes a 64-year-old male with synchronous lung SCC and gastric adenocarcinoma who achieved long-term disease control with Sintilimab monotherapy. Initial imaging and biopsy confirmed poorly differentiated lung SCC (PD-L1 CPS: 2), while PET-CT and endoscopy identified a gastric lesion later confirmed as adenocarcinoma (PD-L1 CPS: 5). Despite indications for chemotherapy, the patient declined cytotoxic therapy and initially refused surgery. He was treated with Sintilimab plus Anlotinib, resulting in lung lesion regression. Progression of gastric obstruction led to gastrectomy two years later; subsequent lung recurrence was managed surgically. Both tumors showed high proliferative indices (Ki-67 ~80–90%) and PD-L1 expression, supporting responsiveness to immune checkpoint blockade. This case highlights the feasibility of immune monotherapy in managing complex synchronous malignancies, especially when standard treatments are declined.